Telomere length associations with cognition depend on Alzheimer's disease biomarkers. Issue 1 (1st January 2019) - Mahoney, Emily R.; Dumitrescu, Logan; Seto, Mabel; Nudelman, Kelly N.H.; Buckley, Rachel F.; Gifford, Katie A.; Saykin, Andrew J.; Jefferson, Angela J.; Hohman, Timothy J.; ,
Abstract: Introduction: While telomere shortening, a marker of cellular aging, may impact the progression of age‐related neurodegenerative diseases, its association with cognition is unclear, particularly in the context of Alzheimer's disease (AD) pathology. Methods: Telomere, cognitive, and CSF data from 482 participants in the AD Neuroimaging Initiative (148 cognitively normal, 283 mild cognitive impairment, 51 AD) was leveraged to assess telomere length associations with cognition (measured by memory and executive function) and interactions with CSF amyloid‐β, tau, and APOE ‐ε4 . Secondary analyses assessed brain volume and thickness outcomes. Results: Longer telomeres at baseline were associated with faster executive function decline. Amyloid‐β and tau interacted with telomere length on cognition, with longer telomeres related to faster decline among biomarker‐positive individuals. Discussion: Telomere associations with cognition shift with AD progression, with longer telomeres related to worse outcomes as pathology increases, highlighting the need for further investigation of telomere length along the AD neuropathological cascade.